Interrelationships between sarcopenia, bone turnover markers and low bone mineral density in patients on hemodialysis. Issue 1 (31st December 2023) - Wang, Yilin; Ma, Wenxia; Pu, Jianhong; Chen, Fengling
Abstract: Background: Hemodialysis (HD) patients are at risk for sarcopenia (SP) and bone loss, which may impact falls and bone fragility and lead to poor prognosis. Patients with HD and those with osteoporosis (OP) are still underdiagnosed and untreated. The aims of the present study were to evaluate the factors that affect bone mineral density (BMD) loss in HD patients, and explore traditional and novel approaches to manage chronic kidney disease–mineral-bone disorder (CKD-MBD). Methods: Patients who underwent regular HD at the First Affiliated Hospital of Soochow University were retrospectively evaluated. According to the WHO osteoporosis criteria, patients were categorized into three groups: normal BMD, osteopenia, and osteoporosis. Demographic and clinical data, skeletal muscle mass, and bone turnover markers(BTM) were compared between the three groups. The correlation between bone density and muscle mass was calculated, and related risk factors were analyzed. Results: This study enrolled 130 HD patients, 36 patients were diagnosed with sarcopenia (27.7%), 44 patients were diagnosed with osteopenia (33.8%), 19 patients were diagnosed with osteoporosis (14.6%), and 23 patients were diagnosed with osteosarcopenia (17.7%). The SMI was positively correlated with the BMD of the lumbar spine ( r  = 0.23, p  < 0.01) and femoral neck ( r  = 0.22, p  < 0.05). In ordinal logistic regression analysis, the odds ratio (OR) for low BMD was high for patients with sarcopenia (OR = 5.894, 95% CI 1.592–21.830, p  < 0.01), older age (OR = 1.095, 95% CI 1.041–1.153, p  < 0.001), higher TRACP-5b levels (OR = 1.597, 95% CI 1.230–2.072, p  < 0.01), and lower 25-OH vitamin D levels (OR = 0.631, 95% CI 0.544–0.733, p  < 0.001). Conclusion: The preservation of skeletal muscle mass could be important to prevent a BMD decrease in HD patients. Adequate intake of vitamin D and control of TRACP-5b levels will help reduce the occurrence and progression of osteopenia/sarcopenia in HD patients.